The Right to Housing in the New Constitution of Chile: International experiences and reflections (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
Chile is drafting a new Constitution with the view of organising and distributing economic and political power in a fairer manner, and that guarantees the rights of all individuals and communities on an equal fashion. The aim of this essay is to offer an analysis of the right to adequate housing in the context of the constitutional process in Chile, from the perspective of international human rights law and comparative constitutional experiences. The elements and principles that we consider have the potential to guide the constitutional discussion in the context of the urban apartheid that the country is experiencing.
Keywords: right to housing; human rights; urban spatial segregation; commodification